OESTROGENS AND PROLACTIN REGULATE MAMMARY GLAND EPITHELIAL CELL GROWTH BY MODULATION OF THE WNT SIGNAL PATHWAY - Jinjin Tong; Hua Zhang; Yuhong Wu; Yingxue Wang; Qingzhang Li; Yun Liu (Slovenski veterinarski zbornik, 2016)
Estrogen and prolactin can regulate mammary gland development and epithelial cell growth as well as lactation.  Meanwhile, the Wnt signaling pathway and subsequent upregulation of b-catenin driven by downstream target of cyclinD1 also play a role in development of mammary gland. This study aimed to assess the possible involvement of estrogen and prolactin in regulation of cell growth in mammary gland. Bovine mammary gland epithelial cells (MECs) were treated with estrogen and prolactin (5 µg mL-1) respectively for 48 h and then measured for cell viability. mRNA and protein expression level of genes (E-cadherin, CyclinD1 and b-catenin) related with Wnt pathway were measured by qRT-PCR and Western blot respectively while sub-cellular localizations of the proteins in MECs were further monitored by immunoﬂuorescence. Expression of E-cadherin and CyclinD1 were most highly expressed at 36 h (P<0.05) whereas b-catenin was most lowly expressed at 36 h after treatment with estrogen and prolactin, respectively. Protein level of the E-cadherin and cyclinD1, which are the targets of Wnt signal pathway, were unregulated. b-catenin protein level was decreased in both hormone groups. In conclusion, prolactin and estrogen could efficiently affect cell growth of MECs and increase the expression of E-cadherin and cyclinD1 at both mRNA and protein level. Immunoﬂuorescence suggested that prolactin and estrogen impact the nuclear expression of b-catenin protein. Our current study indicated that the proliferative efﬁcacy of prolactin and estrogen on MECs was modulated through Wnt signaling pathway.